Surgical Anatomy for Extended Facelift Techniques - Cakmak, Ozcan; Emre, Ismet Emrah (Facial Plastic Surgery, 2020)
Preservation of the facial nerve is crucial in any type of facial procedure. This is even more important when performing plastic surgery on the face. An intricate knowledge of the course of the facial nerve is a requisite prior to performing facelifts, regardless of the technique used. The complex relationship of the ligaments and the facial nerve may put the nerve at an increased risk of damage, especially if its anatomy is not fully understood. There are several danger zones during dissection where the nerve is more likely to be injured. These include the areas where the nerve branches become more superficial in the dissection plane, and where they traverse between the retaining ligaments of the face. Addressing these ligaments is crucial, as they prevent the transmission of traction during facelifts. Without sufficient release, a satisfying pull on the soft tissues may be limited. Traditional superficial musculoaponeurotic system techniques such as plication or imbrication do not include surgical release of these attachments. Extended facelift techniques include additional dissection to release the retaining ligaments to obtain a more balanced and healthier look. However, these techniques are often the subject of much debate due to the extended dissection that carries a higher risk of nerve complications. In this article we aim to present the relationship of both the nerve and ligaments with an emphasis on the exact location of these structures, both in regard to one another and to their locations within the facial soft tissues, to perform extended techniques safely.
Keywords: facelift; deep plane; composite plane; retaining ligament; facial nerve